2011
DOI: 10.1159/000321242
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of <i>bla</i><sub>CTX-M</sub> Genes Carried by Clinically Significant <i>Escherichia coli</i> Isolates in Kuwait Hospitals

Abstract: Objective: To investigate the extent, distribution and sequence analysis of blaCTX-M genes carried by Escherichia coli isolated from patients admitted to all government hospitals in Kuwait. Methods: Extended-spectrum β-lactamase (ESBL)-producing E. coli isolates were collected from the 8 major hospitals in Kuwait. CTX-M ESBLs were analyzed by PCR and sequenced. Clonality of the positive isolates was determined for genetic relatedness using pulsed-field gel electrophoresis (PFGE) with XbaI digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
4
9
0
Order By: Relevance
“…Unsurprisingly, urine samples were the major source (78.9%) of the resistant bacteria. This study also showed that while the majority of CTX-M-producing E. coli isolates have been found among Kuwaiti nationals, patients belonging to other nationalities have also contributed significantly (77). Of 16 randomly selected ESBL-producing K. pneumoniae isolates and 27 E. coli isolates, CTX-M-15 was found in 10 out of 11 bla CTX-M -positive K. pneumoniae and 19 out of 21 bla CTX-M -positive E. coli strains isolated between 2005 and 2006.…”
Section: Extended-spectrum and Ampc-type ␤-Lactamasessupporting
confidence: 55%
“…Unsurprisingly, urine samples were the major source (78.9%) of the resistant bacteria. This study also showed that while the majority of CTX-M-producing E. coli isolates have been found among Kuwaiti nationals, patients belonging to other nationalities have also contributed significantly (77). Of 16 randomly selected ESBL-producing K. pneumoniae isolates and 27 E. coli isolates, CTX-M-15 was found in 10 out of 11 bla CTX-M -positive K. pneumoniae and 19 out of 21 bla CTX-M -positive E. coli strains isolated between 2005 and 2006.…”
Section: Extended-spectrum and Ampc-type ␤-Lactamasessupporting
confidence: 55%
“…The heterogeneous natures of these enzymes were reported by Al Hashem et al (16), and Khanna et al (23). The rapid dissemination of non-clonal multi-resistant CTX-M-1 producing E. coli isolates indicates the need for further investigations in medical centers.…”
Section: Discussionmentioning
confidence: 85%
“…Obviously, our results were analyzed based on the new 2010 CLSI interpretative criteria (10). A high incidence of ESBL-producers amongst E. coli was reported from India (79%), Pakistan (64%) and Kuwait (77.9%) (16)(17)(18). These studies indicate a high incidence of ESBL-producers amongst E. coli isolates in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…In recent reports from the UAE and Kuwait, the proportions of Enterobacteriaceae isolates with the CTX-M genotype were 87 and 77.9%, respectively [16,17]. Lower figures have emerged from Saudi Arabia, with two recent reports showing bla CTX-M detection in 34 and 71% of Enterobacteriaceae isolates [14,18].…”
Section: Discussionmentioning
confidence: 99%